2006
DOI: 10.1016/j.cell.2006.05.052
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for High-Mobility Group A Proteins in Cellular Senescence and Heterochromatin Formation

Abstract: Cellular senescence is a stable state of proliferative arrest that provides a barrier to malignant transformation and contributes to the antitumor activity of certain chemotherapies. Senescent cells can accumulate senescence-associated heterochromatic foci (SAHFs), which may provide a chromatin buffer that prevents activation of proliferation-associated genes by mitogenic transcription factors. Surprisingly, we show that the High-Mobility Group A (HMGA) proteins, which can promote tumorigenesis, accumulate on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
584
5
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 542 publications
(625 citation statements)
references
References 40 publications
33
584
5
3
Order By: Relevance
“…In fact, Hmga1/2 DKO MEFs repair DNA less efficiently than wild-type MEFs following IR exposure. Moreover, we show that Hmga1/ 2 DKO MEFs fail to undergo stress-induced senescence following IR treatment, further supporting the previously reported role of HMGA proteins in the process of cellular senescence (Narita et al, 2006). We hypothesize that reduced levels of ATM observed in Hmga1/2 DKO cells may be, at least in part, responsible of this phenotype.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, Hmga1/2 DKO MEFs repair DNA less efficiently than wild-type MEFs following IR exposure. Moreover, we show that Hmga1/ 2 DKO MEFs fail to undergo stress-induced senescence following IR treatment, further supporting the previously reported role of HMGA proteins in the process of cellular senescence (Narita et al, 2006). We hypothesize that reduced levels of ATM observed in Hmga1/2 DKO cells may be, at least in part, responsible of this phenotype.…”
Section: Discussionsupporting
confidence: 90%
“…[31]. HMGA proteins are essential structural components of senescence-associated heterochromatic foci (SAHFs).…”
Section: Trail Induced Senescence-like Phenotype (Slp) Of Tumor Cellsmentioning
confidence: 99%
“…HMGA proteins are essential structural components of senescence-associated heterochromatic foci (SAHFs). HMGA proteins cooperate with the p16 INK4a promote SAHF formation and proliferative arrest and stabilize senescence by contributing to the repression of proliferation-associated genes [31]. H460, OVCAR-3 and MCF-7 cells were treated with 500 ng/ml TRAIL for 4h.…”
Section: Trail Induced Senescence-like Phenotype (Slp) Of Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 These heterochromatin foci are hallmarked by H3K9me3 and the incorporation of heterochromatin protein HP1, macroH2A, PML (promyelocy leukemia protein) and HMGA1 (high mobility group AT-hook 1). 7,[9][10][11] Recently, it has been shown that repressive markers, such as H3K9me3, H3K9me2 and H3K27me3, are rearranged into the nonoverlapping structural layers in SAHF. [12][13][14] Changes of heterochromatin organization generate a repressive chromatin environment that prevents transcription of genes that promote growth, thereby stabilize the state of senescence.…”
mentioning
confidence: 99%